2007
DOI: 10.1080/01635580701274046
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Lycopene Supplementation in Tobago Men with High Prostate Cancer Risk

Abstract: This unblinded, randomized, Phase I clinical trial was conducted to determine whether lycopene supplementation lowered serum prostate specific antigen (PSA), surrogate endpoint for prostate cancer initiation or progression, in men with elevated prostate cancer risk. Afro-Caribbean men (n=81) with high-grade prostatic intraepithelial neoplasia, atypical foci or repeated non-cancerous biopsies, ascertained in a population-based screening program, were randomized to four months intervention with 30 mg/day lycopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 17 publications
2
37
0
2
Order By: Relevance
“…More importantly, the level of lycopene here is still well below that seen in adults taking a lycopenebearing antioxidant supplement as described in Bunker et al, (2007). Taking into account that significant differences in lycopene uptake among organs, tissues and cell types (Khachik et al, 2002;Liu et al, 2006) can occur, the concentration used in this study is compatible with the physiological levels, and is consistent with the lycopene intake that could be obtained from a standard (albeit Mediterranean) diet.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…More importantly, the level of lycopene here is still well below that seen in adults taking a lycopenebearing antioxidant supplement as described in Bunker et al, (2007). Taking into account that significant differences in lycopene uptake among organs, tissues and cell types (Khachik et al, 2002;Liu et al, 2006) can occur, the concentration used in this study is compatible with the physiological levels, and is consistent with the lycopene intake that could be obtained from a standard (albeit Mediterranean) diet.…”
Section: Discussionsupporting
confidence: 71%
“…It has to be remarked that the level of lycopene used in this study (30.4 ng/ml) is near or below those commonly seen in the serum of adult humans (i.e., 28-31, 54-86, or 170-190 ng/ml), depending on population being studied (Anderson et al, 2006;Riccioni et al, 2007;Bunker et al, 2007). More importantly, the level of lycopene here is still well below that seen in adults taking a lycopenebearing antioxidant supplement as described in Bunker et al, (2007).…”
Section: Discussionmentioning
confidence: 99%
“…Around the globe federal and government efforts have accumulated on consensus for statutory policy to use nutraceuticals on their daily requirements, supplementation, combinations and dosage to prevent or manage the cancer [79][80][81][82][83]. Randomized and double blind control trials indicated the increased importance of vitamins, herbs and fresh vegetables as likely protective supplements [84][85][86][87][88][89][90], tomato (lycopene) in prostate cancer prevention [91][92][93], nutritional intervention in different cancers of different body organs in the body [94][95][96][97][98][99][100]. New concept of Mediterranean diet was introduced to reduce the risk of cancer along with cardioprotection [101][102][103][104].…”
Section: Nutraceuticals In Cancer Prevention During Years 2002-2008mentioning
confidence: 99%
“…As the bond between lycopene and macromolecules within the food-matrix is comparatively strong, its bioavailability from dietary sources is rather remote, but can be enhanced by processing the food, like cooking or chopping, in order to separate complexes between lycopene and protein [76,100]. The food matrix, to which lycopene is tightly attached, is thought to contribute to the maintenance of a stable all-trans isomer, thereby preventing the molecule to isomerize to the cis-conformation.…”
Section: Bioavailability and Metabolism Of Lycopenementioning
confidence: 99%